2021
DOI: 10.1021/acs.molpharmaceut.1c00455
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Fibroblast-Targeting Nanoparticles for Enhancing Solid Tumor Therapy: Progress and Challenges

Abstract: Even though nanoparticle drug delivery systems (nanoDDSs) have improved antitumor efficacy by delivering more drugs to tumor sites compared to free and unencapsulated therapeutics, achieving satisfactory distribution and penetration of nanoDDSs inside solid tumors, especially in stromal fibrous tumors, remains challenging. As one of the most common stromal cells in solid tumors, tumor-associated fibroblasts (TAFs) not only promote tumor growth and metastasis but also reduce the drug delivery efficiency of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 170 publications
0
16
0
Order By: Relevance
“…CAFs are the most abundant stromal cells in the TME, which produce excessive collagen deposition to hinder intra-tumoral deep penetration of nanoparticles [ 24 ]. Herein, we investigated whether CFH/OM-L could inhibit the collagen secretion of CAFs in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…CAFs are the most abundant stromal cells in the TME, which produce excessive collagen deposition to hinder intra-tumoral deep penetration of nanoparticles [ 24 ]. Herein, we investigated whether CFH/OM-L could inhibit the collagen secretion of CAFs in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, model nanotoxicity studies based on non-mammalian alternatives to the C. elegans platform are rather promising for technological advances and regulatory scientific research for handling, labeling, testing toxicity, and evaluating the environmental impact of nanoparticles [ 39 ].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The nanoparticle targeting CAF could reshape the TME or CAF and enhance drug delivery efficiency into tumor cells. Currently, several CAF-targeting nanoparticles have been reported that accomplished antitumor effects by eradicating CAF or reshaping the CAF functions [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…RES had been used to interrupt crosstalk between CAF and cholangiocarcinoma cells and thus inhibit cell invasion of the cholangiocarcinoma cells [ 34 ]. Numerous studies have reported that resveratrol inhibits cell proliferation of cancer cells and tumor growth in vitro and in vivo in breast, colon, prostate, and lung cancers [ 24 , 35 , 36 ]. Unfortunately, clinical trials showed unsatisfactory results with no effect on tumor growth [ 28 ].…”
Section: Introductionmentioning
confidence: 99%